2020
DOI: 10.7860/jcdr/2020/44296.13846
|View full text |Cite
|
Sign up to set email alerts
|

An Aggressive Urothelial Carcinoma in a Horseshoe Kidney- A Case Report

Abstract: Evidence of horseshoe kidney in Indian population is 1 in 600-800 individuals. Horseshoe kidney is predisposed to complications by virtue of its ectopic position, malrotation and associated vascular and ureteral anomalies. Incidence of Renal Cell Carcinoma (RCC) in a horseshoe kidney is same as that in general population. Other pelvic tumours, transitional tumours, Wilms tumour and carcinoids show a greater frequency. High grade urothelial carcinomas are quite rare with a few case reports available. An index c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Balawender et al reported that renal cell carcinoma was the most commonly detected tumour, followed by Wilms tumour and transitional cell carcinoma. 7 TCRCC has often been confused with other cystic lesions of the kidney like cystic nephroma (CN), mixed epithelial and stromal tumour (MEST) and multilocular cystic renal neoplasm of low malignant potential (MCNLMP). CN and MEST have a female predominance.…”
Section: Discussionmentioning
confidence: 99%
“…Balawender et al reported that renal cell carcinoma was the most commonly detected tumour, followed by Wilms tumour and transitional cell carcinoma. 7 TCRCC has often been confused with other cystic lesions of the kidney like cystic nephroma (CN), mixed epithelial and stromal tumour (MEST) and multilocular cystic renal neoplasm of low malignant potential (MCNLMP). CN and MEST have a female predominance.…”
Section: Discussionmentioning
confidence: 99%
“…It involves the two kidneys being fused at their lower poles by the isthmus, a region consisting of fibrous tissue and parenchyma [ 6 ]. According to the current literature, renal cell carcinoma (RCC) is considered the most common type of tumor in the horseshoe kidney, with an incidence no higher than the normal population [ 5 ]. However, renal pelvis UC is more frequent in cases with horseshoe kidneys than in the normal population possibly due to the increased risk of chronic obstruction, increased prevalence of renal calculi, and recurrent urinary infection [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are 200 reported cases of tumors in the horseshoe kidney. Balawender K et al reported that the most common tumor detected is RCC, which constitutes 45% of the tumors, followed by Wilms and TCC, accounting for 20% of tumors in the horseshoe kidney [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation